Towards label-free, wash-free and quantitative B-type natriuretic peptide detection for heart failure diagnosis. Issue 39 (1st October 2019) - Li, Zhi; Ausri, Irfani R.; Zilberman, Yael; Tang, Xiaowu (Shirley)
Abstract : A unique integrated system demonstrating a significant step beyond proof-of-concept high sensitivity carbon nanotube based sensors for quantitative reading of B-type natriuretic peptide (BNP) in outpatient blood is presented. Abstract : Current diagnostic systems used in clinical settings to detect protein biomarkers require highly trained experts, large volumes of blood samples, and long turnaround times. There is an immense need for a low-cost and accurate point-of-care-testing (POCT) device for home monitoring of protein biomarkers for global pandemics such as heart failure (HF). The integration of highly sensitive carbon nanotube (CNT) thin film (CNT-TF) impedance sensors with the electrochemical impedance spectroscopy (EIS) technique is a promising platform to actualize POCT systems for home use. Herein, we report such a system, NanoBot, which allows the label-free and wash-free detection of the HF antigen biomarker B-type natriuretic peptide (BNP) in blood plasma. The NanoBot system consists of two parts: a disposable test strip and a miniature electronic readout unit. The NanoBot exhibited reasonable accuracy and precision, a clinically relevant limit of detection (LOD) as low as 16 pg mL −1, a linear detection range from 0–4000 pg mL −1 and excellent correlation with a reference standard fluorescent immunoassay (FIA). A pilot clinical study with patient-derived blood plasma validated the NanoBot's strong performance compared to that of Alere Triage®, with an interclass correlation coefficient (ICC) of 98% and a square of correlation coefficient (CC) of 0.95. Furthermore, unlike the Alere Triage® that requires more than 250 μL of blood collected via venipuncture, the NanoBot only requires 50 μL of blood. Collectively, the NanoBot's high sensitivity, accuracy, precision, and self-calibration characteristics signify its promising potential as a POCT platform for heart failure diagnosis in home use.